MATERIALISM, HEDONISM, SPIRITUALITY, AND SUBJECTIVE WELL-BEING: AN EMPIRICAL STUDY OF RISALE-I NUR (RN) READERS - Aydin, Necati; Manusov, Eron (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2016)
Since the Enlightenment, particularly in the West, the quest for happiness has been primarily sought through material consumption. Although global capitalism has been successful in producing more wealth, many studies reveal that more wealth and consumption have not increased human happiness. Muslim scholar, Said Nursi, has argued that this failure to achieve happiness is due to the adherence to hedonic and materialist values at the expense of spiritual and moral values. He links the success of the Islamic exegesis, the Risale-i Nur (RN) to its novel approach to happiness. The purpose of this empirical study is to determine whether pleasures of Paradise or true happiness are more likely attained with a life that focuses on good deeds, virtues and spirituality. We designed and conducted a comprehensive internet-based electronic survey among 1523 Risale-i Nur readers to test Nursi’s argument. The survey was designed to capture the values/goals of RN readers and their subjective well-being through over 100 questions. The survey included the Satisfaction with Life Scale, the Social Well-Being Scale, and the Aspiration Index as well as additional items that queried three additional domains of intellectual life, honesty and fairness, and aesthetical life. The study reveals that the more participants read the RN, the more they report the value of spirituality, fairness and honesty, family and friendship, intellectual activities, personal growth, aesthetics experience, conformity, altruism, and health. Conversely, the more they read the RN, the less they value hedonic pleasures, popularity and fame, money and material gains, image making, and fear and anxiety.